Effect of Earnings Per Share, Current Ratio And Return On Equity On Share Price In Property And Real Estate Companies Listed On The Indonesia Stock Exchange In 2018-2021 - Tias Penget Wigati; Isma Krisnanto; Diah Wuriah Ningsih (Return : Study of Management, Economic and Bussines, 2022)
The purposes of this study are To find out and analyze the effect of Earning Per Share (EPS), Current Ratio (CR), and Return On Equity (ROE) on stock prices in property and real estate companies on the Indonesia Stock Exchange. The technique of collecting research data is through financial data, while the number of samples used is 32 financial data. The sampling technique used a purposive sampling method with a non-random sampling technique. The test instruments used to test the research instruments are the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and multiple linear regression test. Hypothesis testing was carried out using a t-test, f-test, and coefficient of determination (R2). The results showed that the earnings per share variable had a significant effect on stock prices in property and real estate companies of 0,938, with a significance of 0.000, and the t-count value of 15,403 was greater than t-table 2.045. The current ratio variable has no effect on stock prices in property and real estate companies of 0,091, with a significance of 0,134, the tcount value of 1,544 is smaller than 2.045. The return on equity variable has a significant and significant effect on stock prices in property and real estate companies of 0,111, with a significance of 0.000, the value of count -2,302 is more significant than 2.045. Earnings per share, current ratio, and return on equity variables have a significant effect on stock prices simultaneously in property and real estate companies with a significance value of 0.000 and a Fount value of 149,030 which is greater than F table 2.95.